ALTERNATIF KEBIJAKAN RENEGOSIASI PERJANJIAN KEMITRAAN PLASMA PADA KONFLIK LAHAN DESA UPANG JAYA - Dekha Ariansyah; Sarmila; Junaidi; Desta Natalia; Dwi Alverina Prastia (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to formulate policy recommendations for resolving the oil palm plasma land conflict between the community of Upang Jaya Village and PT Trans Pasific Agro Industry (TPAI) in Banyuasin Regency, South Sumatra. A qualitative descriptive method was employed. Data were collected through a literature review, interviews with residents and village officials of Upang Jaya, and documentation from media sources and academic articles. Policy analysis was conducted using William N. Dunn’s evaluation criteria, including effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The findings indicate that Banyuasin Regent Decree Number 477 of 2012 has not been optimally implemented in delivering benefits to the plasma community. Based on the evaluation results, three policy alternatives were formulated, cross-sectoral coordination, revision or renegotiation of the plasma partnership agreement, and agrarian reform. The assessment shows that revising or renegotiating the plasma partnership agreement is the most feasible and realistic policy alternative.